The principles of language study - Palmer, Harold E. (London Oxford University Press, 1964)
Two twelve-year-old sleuths solve nine puzzling cases, using sketches of important clues. Includes hints for interpreting clues and brief explanations of the investigative methods used.
Keywords: Language and languages -- Study and teaching. Mystery and detective stories. Literary recreations